Effectiveness of Distance Education During Covid-19 at Higher Education Level: Perceptions of Students - Safeer Ijaz; Muhammad Munir Kayani; Syed Ghazanfer Abbas (PT FORMOSA CENDEKIA GLOBAL, 2023)
In the present era of information technology, distance education or online education has been referred to as the method of content dissemination and quick learning technique. Distance education is a key component of education in the 21st century. The birthplace of distance education is the United States of America (USA) and then expanded over worldwide after 1998. The main purpose of this study was to investigate the effectiveness of distance education during COVID-19 at higher education and perceptions of students. This research was conducted to achieve objectives which were: to study the students’ perceptions of effectiveness about distance education during the outbreak of COVID-19 at the higher education, to find out the effect on students perceptions about effectiveness of distance education during the outbreak of COVID-19 at the higher education, and to determine different problems faced by students of distance education during the outbreak of COVID-19 at higher education. The quantitative research approach was used to analyze this research study and the population of the study was comprised of 153 students of BS level Spring Semester 2020 at Faculty of Social Sciences, National University of Modern Languages Islamabad. The sample has been collected through Universal Sampling techniques. Closed-ended five points Likert Scale questionnaire was used to collect data from the selected population. The reliability of the instruments was checked through Cronbach's Alpha which was 0.81. Data were collected through online Google survey forms. Collected data were analyzed through specific statistical software, IBM-SPSS (Version 23). The Frequency and Percentage techniques were used to analyze the data. The results were obtained in the form of tables. The final results showed that respondents had positive perceptions about distance education and it may be continue, respondents indicated the issue of non-availability of distance learning resources and gadgets and these may be provided. Poor internet connection, load shedding, lack of social interactions during distance learning and health risks were also identified in the finding and these may be countered by proper planning and training